2000
DOI: 10.1055/s-2000-6301
|View full text |Cite
|
Sign up to set email alerts
|

(Alkylthio)alkynes as Addends in the Co(0) Catalyzed Intramolecular Pauson-Khand Reaction. Substituent Driven Enhancements of Annulation Efficiency and Stereoselectivity

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 5 publications
0
25
0
2
Order By: Relevance
“…The following compounds have been described: a) Starting enynes: 1, [39] 4, [2a,b] 6, [2c] 7, [40] 8, [41] 10, [2a,b] 12, [2a,b] 16, [42] 18, [13a] 20, [19] 22, [19] 27, [52] 47, [43] 48, [44] 49, [4a] 58, [44] 67, [45] 72 a, [46] 71 b, [47] 75, [2a,b] 79, [8] and 84; [48] b) carboand heterocycles: 2 a, [2a,b] 5, [2a,b] 9, [8] 11, [2a,b] 13 a, [2a,b] 17, [2a,b] 19, [2a,b] 21, [49] 23, [50] 51, [51] 52, [10a] 53, [52] 54, [2a,b] 56, [44] 59, [29] 60, [52] 62, [52] 68, [10b] 69, [10b] 73 a, [53] 76, [54] 77, [55] 78, [10] 79, [8] 81, [53] 89, [53] 90, [53] and 91. [56] Synthesis of new enynes (E)-1,1-Bis(phenylsulfonyl)-4,8-dimethylnona-3,7-diene: Bis(phenylsulfonyl)methane (500 mg, 1.68 mmol) was added at 0 8C to a suspension of NaH (68 mg, 1.68 mmol, 60 % in mineral oil) ...…”
Section: Methodsmentioning
confidence: 99%
“…The following compounds have been described: a) Starting enynes: 1, [39] 4, [2a,b] 6, [2c] 7, [40] 8, [41] 10, [2a,b] 12, [2a,b] 16, [42] 18, [13a] 20, [19] 22, [19] 27, [52] 47, [43] 48, [44] 49, [4a] 58, [44] 67, [45] 72 a, [46] 71 b, [47] 75, [2a,b] 79, [8] and 84; [48] b) carboand heterocycles: 2 a, [2a,b] 5, [2a,b] 9, [8] 11, [2a,b] 13 a, [2a,b] 17, [2a,b] 19, [2a,b] 21, [49] 23, [50] 51, [51] 52, [10a] 53, [52] 54, [2a,b] 56, [44] 59, [29] 60, [52] 62, [52] 68, [10b] 69, [10b] 73 a, [53] 76, [54] 77, [55] 78, [10] 79, [8] 81, [53] 89, [53] 90, [53] and 91. [56] Synthesis of new enynes (E)-1,1-Bis(phenylsulfonyl)-4,8-dimethylnona-3,7-diene: Bis(phenylsulfonyl)methane (500 mg, 1.68 mmol) was added at 0 8C to a suspension of NaH (68 mg, 1.68 mmol, 60 % in mineral oil) ...…”
Section: Methodsmentioning
confidence: 99%
“…The reaction with N,N-diacylamine Nu8 [20] and carbonate 1c proceeded at 40 8C with a good branched to linear ratio and delivered the desired product 2j with 98% ee (Table 1, entry 11). The propargylation of amines [21] and sulfon-A C H T U N G T R E N N U N G amides [22] with propargylic bromides or mesylates was carried out according to reported general procedures. For the sulfonamides 2a-c and 2e a protocol of Sylvester and Chirik, [21b] which was improved by nucleophilic catalysis with TBAI, was used ( Table 2, en- Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Malacria [11] and Livinghouse [12] have independently used cobalt to effect intramolecular allenic Alder-ene reactions; but the scope of these reactions was not investigated. Sato has performed an allenic Alder-ene reaction to form five-membered rings, using stoichiometric amounts of titanium [13], and Trost has shown that 1,3-dienes can be prepared via an intermolecular Alder-ene reaction between allenes and enones using a ruthenium(II) catalyst [14].…”
Section: Introductionmentioning
confidence: 99%